Alveolysis in deciduous tooth. Case report - Flavia Carolina De Camargo; José Carlos P. Imparato; Karla Mayra Pinto e Carvalho Rezende (Asociación Latinoamericana de Odontopediatría, 2019)
Alveolysis is an asymptomatic and infrequent condition. It occurs when the root of the tooth becomes susceptible to the presence of biofilm and formation of calculi, preventing the process of spontaneous wound healing, causing inflammation and irritation of the surrounding mucosa. The main causes of alveolysis are dental caries and dentoalveolar trauma. In the treatment of alveolysis, immediate exodontia is usually indicated. The present study aims to present a case report of a 5 - year - old female child with alveolysis of primary tooth 51, which was extracted and showed a normal healing process with eruption of successor tooth 11 without alterations. It is up to the dentist to search for information about this pathology, knowing how to identify it and treat it early to significantly improve the child's quality of life.